Contribution of Dr. Vladimir A. Koshkin to the development of plant physiology at VIR - B. V. Rigin; I. G. Loskutov; I. I. Matvienko; Z. A. Shchedrina; R. A. Abdullaev; E. V. Zuev; E. E. Radchenko (Труды по прикладной ботанике, генетике и селекции)
Vladimir Aleksandrovich Koshkin was a prominent representative of the school of plant physiologists at the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR). He introduced his ideas on the mechanisms of photosynthesis intensity as well as the distribution of photoperiod sensitivity and the rate of development among plant species diversity. He was the first to examine in detail and disclose the relationship between the carbon dioxide compensation point and leaf temperature in C3 and C4 plants. According to Dr. Koshkin, there was no change in the sign of the photoperiodic reaction in the generic evolution of Triticum L. and Aegilops L., while the spring forms of bread and durum wheat widespread in the equatorial zone demonstrated weak photoperiod sensitivity. In his work with the resource departments of VIR, Dr. Koshkin was interested in plant breeding problems in the context of developing earlier-ripening cereal cultivars with a certain reaction to the photoperiod. His joint research projects with a number of breeding centers in Russia on this problem proved effective. He participated in collecting missions in Latin American countries (Cuba, Mexico, Colombia, and Brazil) and was awarded a Timiryazev Gold Medal. Dr. Koshkin was the author of 163 scientific publications and had about 20 certificates of authorship and patents for inventions, crop cultivars and lines. Dr. Vladimir Koshkin was quick to perceive the essence of any problem and used adequate modern methods to set up and analyze high-precision experiments.